REGIONAL INEQUALITIES IN HEALTHY LIFE YEARS IN FRANCE: HOW MUCH THE SOCIOECONOMIC AND LONG-TERM CARE CONTEXTS MATTER?. (11th November 2018) - Cambois, E; Carrère, A; Crouzet, M; Laborde, C
Abstract: With large regional variations in mortality and health in developed countries, it is unclear how locally shorter/longer lives combine with unhealthy/healthy lives. Yet it is crucial to address the potential unequal needs for regions to provide long term care (LTC), while managed on local resources in France, as elsewhere. We computed Healthy and Unhealthy Life Years (HLY/ULY) in the hundred French "departments" for men and women aged 60+ in 2014, using the Global Activity Limitation Indicator (Sullivan method): we found a 3.1 year difference between the highest and the lowest regions' ULY in men and 5.0 year in women, reflecting the variation in years with potential LTC needs. We analyzed this variation through meta-regressions, using indicators of regional socioeconomic contexts and LTC provisions. We present how much the local contexts are linked to healthy aging in France and whether LTC provision matches the potential needs related to longer ULY.